Overtraining Dan Cedera Non-Kontak Pada Atlet Basket Remaja Indonesia - Encep Farlan Sutarza; Sucipto Sucipto; Mulyana Mulyana; Dede Rohmat; Zuliza Adha; Bayu Panji Pangestu (Jurnal Sporta Saintika, 2026)
Overtraining and non-contact injuries represent critical issues in the development of adolescent basketball athletes and may compromise long-term performance progression. Overtraining is defined as a maladaptive condition resulting from an imbalance between training load and recovery, whereas non-contact injuries are primarily associated with impaired neuromuscular control and biomechanical risk factors in the absence of external contact. This conceptual article aims to analyze the relationship between overtraining, neuromuscular fatigue, altered movement control, and high-risk biomechanical patterns contributing to non-contact injuries, while outlining practical prevention implications relevant to the Indonesian youth sport context. A narrative review approach was conducted using scientific publications from 2015 to 2025. The findings indicate that high training volume and intensity, early sport specialization, limited program variation, and insufficient load monitoring and recovery strategies contribute substantially to injury risk. The most frequently reported injuries include ankle sprains, anterior cruciate ligament (ACL) injuries, and hamstring strains. Preventive strategies include structured periodization, developmentally appropriate variation in training, load monitoring using session rating of perceived exertion (sRPE), and systematic recovery education.